2012
DOI: 10.1016/j.biocel.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The zinc finger transcription factor ZKSCAN3 promotes prostate cancer cell migration

Abstract: In our previous studies, ZKSCAN3 was demonstrated to be over-expressed in invasive colonic tumor cells and their liver metastases, but minimally expressed in adjacent non-transformed tissues. Further preliminary data showed that ZKSCAN3 was expressed in a majority of prostate cancer patient samples, but not in normal prostate tissues. Moreover, the ZKSCAN3 protein is highly expressed in the PC3 prostate cancer cell line, which has high metastatic potential, but little expression was observed in non-metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 22 publications
0
47
0
1
Order By: Relevance
“…The researchers found that down-regulation of ZKSCAN3 significantly inhibited tumor growth in colon cancer cells, whereas overexpression of ZKSCAN3 produced the opposite effect. In addition, ZKSCAN3 was found to be highly expressed in multiple myeloma [23, 24] and prostate cancer [25]. Through transcriptional activation of cyclin D2 expression, ZKSCAN3 enhanced tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found that down-regulation of ZKSCAN3 significantly inhibited tumor growth in colon cancer cells, whereas overexpression of ZKSCAN3 produced the opposite effect. In addition, ZKSCAN3 was found to be highly expressed in multiple myeloma [23, 24] and prostate cancer [25]. Through transcriptional activation of cyclin D2 expression, ZKSCAN3 enhanced tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Certain proteins encoding specific zincfinger domains have been reported to recognize non-methylated DNA and to recruit chromatin-modifying elements to CpG islands, 50 and there is evidence for the implication of several zincfinger transcription factors in cancer. [51][52][53][54][55] Hypermethylation of ZNF154 has previously been reported by independent sources to occur in bladder, 18,56 breast, 57 head and neck, 58,59 hepatocellular, 60 lung, 29 ovarian, 25,61 prostate, 62 and renal 63 cancers. Still, very little is known about the biological function of the protein encoded by ZNF154, and the possible functional significance Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…ZKSCAN3, a family member of the KRAB and SCAN domaincontaining zinc-finger transcription factors, has been shown to involve the outgrowth of malignancies [3][4][5][6]. It has indeed been documented that overexpression or gene amplification of ZKSCAN3 in tissue specimens correlates with colorectal cancer invasion [4] or prostate cancer metastasis [4], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It has indeed been documented that overexpression or gene amplification of ZKSCAN3 in tissue specimens correlates with colorectal cancer invasion [4] or prostate cancer metastasis [4], respectively. Recently, we demonstrated that ZKSCAN3 knockdown in bladder cancer lines resulted in considerable decreases in cell viability, along with increased apoptosis, as well as in cell migration and invasion [6].…”
Section: Introductionmentioning
confidence: 99%